Lignin-doped montmorillonite hydrogel as well as preparation method and application thereof
The lignin-doped montmorillonite hydrogel prepared through a one-step chemical modification process solves the complex problem of the preparation of adsorbed pollutant materials in the prior art, and achieves efficient removal of nitrogen and phosphorus ions and microplastics in water, with the advantages of low cost and suitable for industrial utilization.
Patent Information
- Application Number
- CN202411939594.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The prior art has complicated processes in preparing adsorbed contaminant materials, and it is difficult to efficiently remove nitrogen, phosphorus ions and microplastics in water at the same time.
Through a one-step chemical modification process, a lignin-doped montmorillonite hydrogel was prepared, and free radical polymerization was carried out by amination of lignin, montmorillonite k-10, methacryloyloxyethyltrimethylammonium chloride, acrylic acid, acrylamide, N,N-methylenebisacrylamide and potassium persulfate to obtain a hydrogel with high adsorption capacity.
It realizes efficient removal of nitrogen, phosphorus ions and microplastics in water bodies, has simple process and low production costs, and is suitable for large-scale industrial utilization.
Smart Images

Figure HDA0005212296200000011 
Figure HDA0005212296200000012 
Figure HDA0005212296200000021
Abstract
Description
Technical Field
[0001] The invention relates to a lignin-doped montmorillonite hydrogel and a preparation method and application thereof, belonging to the field of functional materials. Background Art
[0002] Nitrogen and phosphorus are essential elements for the survival of all living things in nature. However, various nitrogen and phosphorus-containing wastewaters discharged in industrial and agricultural production for a long time have caused serious eutrophication of natural water bodies, thus seriously damaging aquatic ecosystems. Therefore, the efficient removal and recycling of nitrogen and phosphorus pollutants in water bodies has become the key to solving the current problems of eutrophic water body management and sustainable utilization of nitrogen and phosphorus resources. Similarly, with the widespread use of plastic products, microplastics are widely present in environmental media and organisms around the world. They have a wide range of sources, widespread distribution, complex environmental behavior, and potential ecotoxicological effects, posing a serious threat to ecosystems and human health. Therefore, achieving efficient removal and recycling of microplastics in wastewater containing microplastics is crucial to the realization of my country's "dual carbon" goals.
[0003] Hydrogel is considered to be a potential candidate material for wastewater treatment in addition to traditional adsorbents such as zeolite, clay minerals, synthetic resins and activated carbon. Generally speaking, hydrogel has good hydrophilicity, large specific surface area, a large number of porous structures and active adsorption groups or sites, which ultimately lead to strong interactions between pollutant ions and active adsorption sites, thereby improving the removal efficiency of pollutants in wastewater. Natural polymers in biomass, such as lignin, cellulose, chitosan, etc., are widely used as raw materials for preparing hydrogels because of their rich content, environmental friendliness, and biodegradability, thus giving hydrogels good environmental properties.
[0004] Lignin, as one of the main chemical components, is widely present in plants and is a three-dimensional network natural polymer with an aromatic structure. At the same time, the lignin structure contains a large number of active functional groups, such as carboxyl, phenolic and aliphatic hydroxyl groups, which makes lignin easy to process into hydrogels or gives lignin materials limited adsorption capacity. Lignin is considered to be an ideal polymer for preparing hydrogels, because the use of hydrogels not only brings high value to lignin, but also helps to reduce costs and improve the mechanical properties of hydrogels. In addition, it has been confirmed that eutrophic wastewater often contains pollutants such as anions, cations and microplastics at the same time, and lignin-doped hydrogel adsorbents containing only one ionic group cannot remove all pollutants, so they cannot meet the needs of practical utilization. Therefore, it is of great significance to prepare multi-lignin-doped montmorillonite hydrogels to simultaneously recover nitrogen, phosphorus and microplastics in wastewater.
[0005] However, the early process of preparing amphoteric lignin-based hydrogels is relatively complicated, usually requiring two or more synthesis steps. First, water-soluble lignin derivatives are synthesized using lignin as a raw material, and then the lignin derivatives are modified to introduce different groups to obtain amphoteric lignin-based hydrogels. This complex synthesis step is not conducive to the large-scale promotion of amphoteric lignin-based hydrogels in industrial synthesis. Therefore, it is necessary to find a simple and convenient synthesis method to prepare amphoteric lignin-based hydrogels. The present invention prepares an environmentally friendly, efficient, stable and economical lignin-doped montmorillonite hydrogel through a one-step chemical modification process, which is used for the efficient removal of nitrogen and phosphorus ions and microplastics in water bodies. Summary of the invention
[0006] The present invention aims at the deficiencies existing in the prior art in the process of preparing pollutant adsorbing materials, and provides a lignin-doped montmorillonite hydrogel, a preparation method and an application thereof. The present invention uses aminated lignin as a raw material, montmorillonite K-10, methacryloyloxyethyl trimethylammonium chloride, acrylic acid and acrylamide as monomers, potassium persulfate as an initiator, and N,N-methylenebisacrylamide as a crosslinking agent to prepare a lignin-doped montmorillonite hydrogel capable of adsorbing nitrogen and phosphorus ions and microplastic pollutants through a free radical polymerization reaction, with low production cost and good application prospects.
[0007] A method for preparing a lignin-doped montmorillonite hydrogel comprises the following steps: sequentially adding montmorillonite K-10, methacryloyloxyethyl trimethylammonium chloride, acrylic acid, acrylamide, N,N-methylenebisacrylamide and potassium persulfate into an aqueous solution of aminated lignin, stirring the mixture evenly, carrying out a free radical polymerization reaction, and soaking the obtained product in deionized water to obtain a lignin-doped montmorillonite hydrogel.
[0008] In the method of the present invention, the mass volume ratio of aminated lignin to deionized water in the aminated lignin aqueous solution is 0.15 g:5-15 mL.
[0009] Preferably, the mass volume ratio of aminated lignin to deionized water in the aminated lignin aqueous solution is 0.15 g:7 mL.
[0010] In the method of the present invention, the mass ratio of the aminated lignin, montmorillonite K-10, methacryloyloxyethyl trimethyl ammonium chloride, acrylic acid, acrylamide, N,N-methylenebisacrylamide, and potassium persulfate is 0.15g: 0.5-1.5g: 1.0-3.0g: 1.0-3.0g: 0.5-1.5g: 0.01-0.09g: 0.01-0.03g.
[0011] Preferably, the ratio of the aminated lignin, montmorillonite k-10, methacryloyloxyethyl trimethyl ammonium chloride, acrylic acid, acrylamide, N,N-methylenebisacrylamide, and potassium persulfate is 0.15g:1.0g:2.5g:2.5g:1.0g:0.06g:0.02g.
[0012] In the method of the present invention, the stirring condition is magnetic stirring at 200-600 rpm for 10-30 min.
[0013] In the method of the present invention, the free radical polymerization reaction conditions are 40-80° C. for 1-3 hours.
[0014] Preferably, the temperature of the free radical polymerization reaction is 60° C. and the time is 2 hours.
[0015] Furthermore, the free radical polymerization reaction is carried out in an oven.
[0016] In the method of the present invention, the product is immersed in deionized water for 20 to 40 hours.
[0017] Preferably, the product is immersed in deionized water for 24 hours.
[0018] Another object of the present invention is to provide the lignin-doped montmorillonite hydrogel prepared by the above method.
[0019] Another object of the present invention is to provide the use of the above-mentioned lignin-doped montmorillonite hydrogel in the adsorption of nitrogen and / or phosphorus ions and / or microplastics.
[0020] Furthermore, the application of the lignin-doped montmorillonite hydrogel in the adsorption of nitrogen and / or phosphorus ions and / or microplastics can be divided into four cases. The first is the application of lignin-doped montmorillonite hydrogel in the adsorption of nitrogen ions, the second is the application of lignin-doped montmorillonite hydrogel in the adsorption of phosphorus ions, the third is the application of lignin-doped montmorillonite hydrogel in the adsorption of microplastics, and the fourth is the application of lignin-doped montmorillonite hydrogel in the simultaneous adsorption of nitrogen and phosphorus ions and microplastics.
[0021] Furthermore, the specific process of using the lignin-doped montmorillonite hydrogel in the adsorption of nitrogen and / or phosphorus ions and / or microplastics is: mixing the lignin-doped montmorillonite hydrogel with an aqueous solution of nitrogen and / or phosphorus ions and / or microplastics, adsorbing them in a shaker, and after the adsorption, filtering them, and the obtained solid sample is the lignin-doped hydrogel after adsorbing nitrogen and / or phosphorus ions and / or microplastics.
[0022] Preferably, the lignin-doped montmorillonite hydrogel is used for the simultaneous adsorption of nitrogen and phosphorus ions and microplastics.
[0023] In the above technical solution, the adsorption conditions are adsorption at 100-200 rpm for 10-600 min at a temperature of 20-40°C.
[0024] Preferably, the adsorption condition is 25° C. and 150 rpm for 300 min.
[0025] In the above technical solution, the nitrogen ion aqueous solution is one or more of ammonium chloride solution, ammonium sulfate solution and ammonium nitrate solution.
[0026] In the above technical solution, the concentration of the nitrogen ion aqueous solution is 10 to 200 mg N / L.
[0027] Preferably, the concentration of the nitrogen ion aqueous solution is 100 mg N / L.
[0028] Further preferably, the nitrogen ion aqueous solution is an ammonium chloride solution.
[0029] In the above technical solution, the aqueous solution of phosphorus ions is one or more of potassium dihydrogen phosphate solution, dipotassium hydrogen phosphate solution and sodium dihydrogen phosphate solution.
[0030] In the above technical solution, the concentration of the phosphate ion aqueous solution is 10-200 mg P / L.
[0031] Preferably, the concentration of the phosphate ion aqueous solution is 200 mg P / L.
[0032] Further preferably, the aqueous solution of phosphorus ions is a potassium dihydrogen phosphate solution.
[0033] In the above technical solution, the microplastic aqueous solution is one or more of a polystyrene solution, a polypropylene solution and a polyethylene solution.
[0034] In the above technical solution, the concentration of the microplastic aqueous solution is 100 to 1000 mg / L.
[0035] Preferably, the concentration of the polystyrene aqueous solution is 800 mg / L.
[0036] Further preferably, the microplastic aqueous solution is a polystyrene solution.
[0037] In the above technical solution, the mixed solution of nitrogen and phosphorus ions and microplastics is obtained by dissolving nitrogen-containing substances, phosphorus-containing substances and microplastics in deionized water and stirring them evenly.
[0038] Preferably, the mixed solution of nitrogen and phosphorus ions and microplastics is obtained by dissolving ammonium chloride, potassium dihydrogen phosphate and polystyrene in deionized water and stirring the mixture evenly.
[0039] Furthermore, in the mixed solution of nitrogen and phosphorus ions and microplastics, the concentration of nitrogen ions is 10 to 200 mg N / L, the concentration of phosphorus ions is 10 to 200 mg P / L, and the concentration of microplastics is 100 to 1000 mg / L.
[0040] Preferably, the concentration of nitrogen ions in the nitrogen-phosphorus ion mixed solution is 100 mg N / L, the concentration of phosphorus ions is 100 mg P / L, and the concentration of microplastics is 1000 mg / L.
[0041] In the above technical solution, the mass volume ratio of the lignin-doped montmorillonite hydrogel to the nitrogen and / or phosphorus ions and / or microplastic aqueous solution is 0.05 g: 10 to 100 mL.
[0042] Preferably, the mass volume ratio of the lignin-doped montmorillonite hydrogel to the nitrogen and / or phosphorus ions and / or microplastic aqueous solution is 0.05 g:50 mL.
[0043] Beneficial effects of the present invention:
[0044] 1. The method for preparing lignin-doped montmorillonite hydrogel in the present invention is a one-step preparation method. Compared with the two-step or multi-step method, the one-step method has a simple process, low production cost, and is more suitable for large-scale industrial utilization.
[0045] 2. The lignin-doped montmorillonite hydrogel prepared by the present invention contains abundant active sites, has a strong adsorption capacity for nitrogen and phosphorus ions and microplastics, and can adsorb nitrogen and phosphorus ions and microplastics at the same time.
[0046] 3. The lignin used in the present invention is a major byproduct of the papermaking industry, with a wide range of sources and low cost. Montmorillonite is a common natural mineral material with abundant reserves and low price. Compared with some synthetic polymer adsorption materials, lignin-doped montmorillonite hydrogel has greater cost advantages in large-scale applications and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a picture of the lignin-doped montmorillonite hydrogel sample obtained in Example 1.
[0048] Figure 2 This is the SEM spectrum of the lignin-doped montmorillonite hydrogel obtained in Example 1.
[0049] Figure 3 The lignin-doped montmorillonite hydrogel obtained in Example 1 has an effect on the NH4 + 、H2PO 4- Competitive adsorption data of ions and microplastics.
[0050] Figure 4The NH4 + 、H2PO 4- Data graph of adsorption of ions and microplastics.
[0051] Figure 5 The lignin-doped montmorillonite hydrogel (AALH@MMT) obtained in Example 1 and the undoped montmorillonite hydrogel (AALH) obtained in Comparative Example 1 were used to analyze the NH4 + 、H2PO 4- Data graph of adsorption of ions and microplastics. DETAILED DESCRIPTION
[0052] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0053] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0054] Example 1
[0055] A method for preparing a lignin-doped montmorillonite hydrogel comprises the following steps:
[0056] (1) 0.15 g of aminated lignin and 7 mL of deionized water were mixed to obtain a uniform aminated lignin solution, and then 1.0 g of montmorillonite k-10, 2.5 g of methacryloyloxyethyl trimethylammonium chloride, 2.5 g of acrylic acid, 1.0 g of acrylamide, 0.02 g of potassium persulfate and 0.06 g of N,N-methylenebisacrylamide were added in sequence, and magnetic stirring was performed at a speed of 400 rpm for 20 min to completely dissolve the mixture and the air was removed with N2 to obtain a mixed solution;
[0057] (2) The mixed solution obtained in step (1) was transferred to a sealed container and placed in an oven at 60° C. for 3 h for free radical polymerization. The obtained product was immersed in deionized water for 24 h to obtain lignin-doped montmorillonite hydrogel (AALH@MMT) (see Figure 1 and Figure 2 ).
[0058] Application of the above-obtained lignin-doped montmorillonite hydrogel in the simultaneous adsorption of nitrogen and phosphorus ions and microplastics:
[0059] Weigh 0.05 g of the AALH@MMT hydrogel obtained above into a 100 mL conical flask, and then add 50 mL of a mixed solution of ammonium chloride (100 mg N / L), potassium dihydrogen phosphate (100 mg P / L), and polystyrene (1000 mg / L) (the preparation method of the mixed solution is: weigh 0.0382 g of ammonium chloride, 0.0439 g of potassium dihydrogen phosphate, and 0.1000 g of polystyrene into 100 mL of deionized water at the same time, mix well to obtain NH4 + Concentration is 100mg N / L, H2PO4 - A mixed solution of 100 mg P / L and 1000 mg / L polystyrene concentration was prepared, and finally the conical flask was sealed and placed in a constant temperature shaker, shaken at 25 ° C and 150 rpm for 5 hours, and then filtered with a 0.22 μm filter membrane. The obtained solid sample was lignin-doped montmorillonite hydrogel after adsorbing nitrogen and phosphorus ions and microplastics.
[0060] The above-mentioned lignin-doped montmorillonite hydrogel (AALH@MMT) has a good effect on the NH4 + 、H2PO 4- Simultaneous adsorption of ions and microplastics:
[0061] According to the NH4 + 、H2PO 4- The adsorption of nitrogen and phosphorus ions and microplastics by lignin-doped montmorillonite hydrogel was calculated based on the concentration of ions and polystyrene (see Figure 3 ), where NH4 + Ion concentration was determined by Nessler's reagent method, H2PO 4- The ion concentration was determined by ammonium molybdate colorimetry, and the polystyrene concentration was determined by UV spectrophotometry.
[0062] Application of the above obtained lignin-doped montmorillonite hydrogel in adsorbing nitrogen ions:
[0063] Weigh 0.05 g of the AALH@MMT hydrogel obtained above into a 100 mL conical flask, and then add 50 mL of ammonium chloride solution (weigh 0.0382 g of ammonium chloride into 100 mL of deionized water to obtain NH4 + The conical flask was sealed and placed in a constant temperature shaker, shaken at 25 °C and 150 rpm for 5 h, and then filtered with a 0.22 μm filter membrane. The solid sample obtained was the lignin-doped montmorillonite hydrogel after adsorbing nitrogen ions.
[0064] The above-obtained lignin-doped montmorillonite hydrogel (AALH@MMT) has a significant effect on the NH4 + Ion adsorption:
[0065] According to the NH4 + The nitrogen ion adsorption capacity of lignin-doped montmorillonite hydrogel was calculated based on the concentration of Figure 4 ), where NH4 + The ion concentration was determined by Nessler's reagent method.
[0066] Application of the above obtained lignin-doped montmorillonite hydrogel in adsorbing phosphorus ions:
[0067] Weigh 0.05 g of the AALH@MMT hydrogel obtained above into a 100 mL conical flask, then add 50 mL of potassium dihydrogen phosphate solution (weigh 0.0878 g of potassium dihydrogen phosphate into 100 mL of deionized water and mix well to obtain H2PO4 - The conical flask was sealed and placed in a constant temperature shaker, shaken at 25 ° C and 150 rpm for 5 hours, and then filtered with a 0.22 μm filter membrane. The obtained solid sample was the lignin-doped montmorillonite hydrogel after the adsorption of phosphorus ions.
[0068] The above-obtained lignin-doped montmorillonite hydrogel (AALH@MMT) had an effect on the H2PO4 in water at different dosages. 4- Ion adsorption:
[0069] According to the H2PO4 content in aqueous solution before and after adsorption 4- The phosphorus ion adsorption capacity of lignin-doped montmorillonite hydrogel was calculated based on the concentration of Figure 4 ), where H2PO 4- The ion concentration was determined by the ammonium molybdate colorimetric method.
[0070] Application of the above-obtained lignin-doped montmorillonite hydrogel in adsorbing microplastics:
[0071] Weigh 0.05 g of the AALH@MMT hydrogel obtained above into a 100 mL conical flask, and then add 50 mL of polystyrene solution (weigh 0.0800 g of polystyrene into 100 mL of deionized water, mix evenly to obtain a polystyrene solution with a polystyrene concentration of 800 mg / L). Finally, seal the conical flask and place it in a constant temperature shaker, and shake it at 25 ° C and 150 rpm for 5 hours. The obtained solid sample is the lignin-doped montmorillonite hydrogel after adsorbing microplastics.
[0072] Adsorption of polystyrene in water by the above-obtained lignin-doped montmorillonite hydrogel (AALH@MMT) at different dosages:
[0073] The amount of polystyrene adsorbed by lignin-doped montmorillonite hydrogel was calculated based on the concentration of polystyrene in the aqueous solution before and after adsorption (see Figure 4 ), wherein the polystyrene concentration in the filtrate is determined by ultraviolet spectrophotometry.
[0074] Comparative Example 1
[0075] A method for preparing a lignin-undoped montmorillonite hydrogel comprises the following steps:
[0076] (1) 0.15 g of aminated lignin and 7 mL of deionized water were mixed to obtain a uniform aminated lignin solution, and then 2.5 g of methacryloyloxyethyl trimethylammonium chloride, 2.5 g of acrylic acid, 1.0 g of acrylamide, 0.02 g of potassium persulfate and 0.06 g of N,N-methylenebisacrylamide were added in sequence, and the mixture was magnetically stirred at a speed of 400 rpm for 20 min to completely dissolve the mixture, and air was removed with N2 to obtain a mixed solution;
[0077] (2) The mixed solution obtained in step (1) was transferred into a sealed container and placed in an oven at 60° C. for 3 h for free radical polymerization reaction. The obtained product was soaked in deionized water for 24 h to obtain lignin undoped montmorillonite hydrogel (AALH).
[0078] Application of the above obtained lignin undoped montmorillonite hydrogel in adsorbing nitrogen ions:
[0079] Weigh 0.04 g of the AALH hydrogel obtained above into a 100 mL conical flask, and then add 50 mL of ammonium chloride solution (weigh 0.0382 g of ammonium chloride into 100 mL of deionized water to obtain NH4 + The conical flask was sealed and placed in a constant temperature shaker, shaken at 25 °C and 150 rpm for 5 h, and then filtered with a 0.22 μm filter membrane. The solid sample obtained was the lignin-undoped montmorillonite hydrogel after adsorbing nitrogen ions.
[0080] The above obtained lignin undoped montmorillonite hydrogel (AALH) at a dosage of 0.8 g / L was used to treat NH4 + Ion adsorption:
[0081] According to the NH4 + The nitrogen ion adsorption capacity of lignin-undoped montmorillonite hydrogel was calculated based on the concentration of lignin (see Figure 5 ), where NH4 + The ion concentration was determined by Nessler's reagent method.
[0082] Application of the above obtained lignin undoped montmorillonite hydrogel in adsorbing phosphorus ions:
[0083] Weigh 0.02 g of the AALH hydrogel obtained above into a 100 mL conical flask, then add 50 mL of potassium dihydrogen phosphate solution (weigh 0.0878 g of potassium dihydrogen phosphate into 100 mL of deionized water and mix well to obtain H2PO4 - The conical flask was sealed and placed in a constant temperature shaker, shaken at 25 ° C and 150 rpm for 5 hours, and then filtered with a 0.22 μm filter membrane. The solid sample obtained was the lignin undoped montmorillonite hydrogel after the adsorption of phosphorus ions.
[0084] The above obtained lignin undoped montmorillonite hydrogel (AALH) at a dosage of 0.4 g / L was used to treat H2PO4 in water. - Ion adsorption:
[0085] According to the H2PO4 content in aqueous solution before and after adsorption 4- The phosphorus ion adsorption capacity of lignin-undoped montmorillonite hydrogel was calculated based on the concentration of lignin (see Figure 5 ), where H2PO 4- The ion concentration was determined by the ammonium molybdate colorimetric method.
[0086] Application of the above obtained lignin undoped montmorillonite hydrogel in adsorbing microplastics:
[0087] Weigh 0.04 g of the AALH hydrogel obtained above into a 100 mL conical flask, and then add 50 mL of polystyrene solution (weigh 0.0800 g of polystyrene into 100 mL of deionized water, mix evenly to obtain a polystyrene solution with a polystyrene concentration of 800 mg / L). Finally, seal the conical flask and place it in a constant temperature shaker, and shake it at 25 ° C and 150 rpm for 5 hours. The obtained solid sample is the lignin undoped montmorillonite hydrogel after adsorbing microplastics.
[0088] Adsorption of polystyrene in water by the lignin undoped montmorillonite hydrogel (AALH) obtained above at a dosage of 0.8 g / L:
[0089] The amount of polystyrene adsorbed by lignin-undoped montmorillonite hydrogel was calculated based on the concentration of polystyrene in the aqueous solution before and after adsorption (see Figure 5 ), wherein the polystyrene concentration in the filtrate is determined by ultraviolet spectrophotometry.
[0090] Figure 1 This is a picture of the lignin-doped montmorillonite hydrogel sample obtained in Example 1 of the present invention.
[0091] Figure 2This is a SEM spectrum of the lignin-doped montmorillonite hydrogel obtained in Example 1 of the present invention. It can be seen from the figure that the lignin-doped montmorillonite hydrogel presents a three-dimensional porous network structure, which increases the specific surface area of the lignin-doped montmorillonite hydrogel, is conducive to exposing more active sites, and thus provides more channels for the penetration of nitrogen and phosphorus ions and microplastics.
[0092] Figure 3 The lignin-doped montmorillonite hydrogel obtained in Example 1 of the present invention has an effect on the NH4 + 、H2PO 4- Ions and polystyrene competitive adsorption data. It can be seen from the figure that increasing the NH4 + 、H2PO 4- The concentration of one of the ions and polystyrene substances will lead to a decrease in the equilibrium adsorption amount of the other two substances by lignin-doped montmorillonite hydrogel.
[0093] Figure 4 The NH4 + 、H2PO 4- The adsorption data of ions and microplastics. It can be seen from the figure that as the amount of lignin-doped montmorillonite hydrogel increases from 0.20g / L to 0.40g / L, its adsorption of H2PO4 - The equilibrium adsorption of ions reached the maximum value. As the amount of lignin-doped montmorillonite hydrogel increased from 0.20 g / L to 0.80 g / L, its adsorption of NH4 + The equilibrium adsorption amounts of ions and polystyrene both reached their maximum values.
[0094] Figure 5 The results of the lignin-doped montmorillonite hydrogel (AALH@MMT) obtained in Example 1 of the present invention and the lignin-undoped montmorillonite hydrogel (AALH) obtained in Comparative Example 1 on NH4 + 、H2PO 4- Comparison of adsorption data of ions and microplastics. Among them, the adsorption of NH4 + 、H2PO 4- The amount of lignin used for adsorption of ions and microplastics was the same as that of montmorillonite hydrogel without lignin doping. + 、H2PO 4- The equilibrium adsorption amounts of ions and microplastics were higher than those of the hydrogels without montmorillonite.
Claims
1. A method for preparing lignin-doped montmorillonite hydrogel, characterized in that: Montmorillonite K-10, methacryloyloxyethyl trimethylammonium chloride, acrylic acid, acrylamide, N,N-methylenebisacrylamide and potassium persulfate are added to the aminated lignin aqueous solution in sequence, stirred evenly, and a free radical polymerization reaction is carried out. The obtained product is soaked in deionized water to obtain a lignin-doped montmorillonite hydrogel.
2. The preparation method according to claim 1, characterized in that: The mass volume ratio of aminated lignin to deionized water in the aminated lignin aqueous solution is 0.15g:5-15mL; the mass ratio of the aminated lignin, montmorillonite k-10, methacryloyloxyethyl trimethylammonium chloride, acrylic acid, acrylamide, N,N-methylenebisacrylamide, and potassium persulfate is 0.15g:0.5-1.5g:1.0-3.0g:1.0-3.0g:0.5-1.5g:0.01-0.09g:0.01-0.03g.
3. The preparation method according to claim 1, characterized in that: The free radical polymerization reaction conditions are to react at 40 to 80° C. for 1 to 3 hours.
4. The preparation method according to claim 1, characterized in that: The product is immersed in deionized water for 20 to 40 hours.
5. The lignin-doped montmorillonite hydrogel prepared by the method according to any one of claims 1 to 4.
6. Use of the lignin-doped montmorillonite hydrogel according to claim 5 in the adsorption of nitrogen and / or phosphorus ions and / or microplastics.
7. The use according to claim 6, characterized in that: The lignin-doped montmorillonite hydrogel is mixed with an aqueous solution of nitrogen and / or phosphorus ions and / or microplastics, and adsorbed in a shaker. After the adsorption is completed, the mixture is filtered to obtain a solid sample, which is the lignin-doped hydrogel after adsorbing nitrogen and / or phosphorus ions and / or microplastics.
8. The use according to claim 7, characterized in that: The adsorption conditions are: adsorption at 100-200 rpm for 10-600 min at a temperature of 20-40°C.
9. The use according to claim 7, characterized in that: The nitrogen ion aqueous solution is one or more of ammonium chloride solution, ammonium sulfate solution and ammonium nitrate solution; The phosphate ion aqueous solution is one or more of potassium dihydrogen phosphate solution, dipotassium hydrogen phosphate solution and sodium dihydrogen phosphate solution; The microplastic aqueous solution is one or more of a polystyrene solution, a polypropylene solution and a polyethylene solution.
10. The use according to claim 7, characterized in that: The concentration of the nitrogen ion aqueous solution is 10-200 mg N / L; the concentration of the phosphorus ion aqueous solution is 10-200 mg P / L; the concentration of the microplastic aqueous solution is 100-1000 mg / L; The mass volume ratio of the lignin-doped montmorillonite hydrogel to the nitrogen and / or phosphorus ion and / or microplastic aqueous solution is 0.05 g:10-100 mL.
Citation Information
Patent Citations
Preparation method of soil amendment capable of controlling soil erosion
CN102477300A
Polymer hydrogel capable of absorbing heavy metal ions and preparation method of polymer hydrogel
CN103102453A
Preparation method of double ionic straw based hydrogel applied for sewage treatment
CN104826604A
Bio-based amphoteric polymer as well as preparation method and application thereof
CN113831480A
Preparation method of adsorption type degradable soil moisture preservation slow release fertilizer based on modified wheat straw
CN114920606A
Cited By
Sodium alginate-montmorillonite coated mango leaf biochar material as well as preparation method and application thereof
CN121695829A